Cercospora spp : identificação morfológica e molecular, patogenicidade, sensibilidade a fungicidas e reação de cultivares de soja - Silva, Monikéli Aparecida da (2022)
Purple seed stain (PSS) and Cercospora leaf blight (CLB) are soybean diseases commonly associated with the phytopathogen Cercospora kikuchii, but other species have been associated such as C. cf. flagellaris, C. cf. sigesbeckiae and C. nicotianae. The management of these diseases includes cultural and chemical methods, the latter being necessary to monitor the efficiency of fungicides. For genetic control, there is no evidence of resistant cultivars, being necessary to perform the reaction of soybean cultivars to these phytopathogens. Considering the importance of PSS and CLB in soybean crop and the scarcity of information on Cercospora species, the objectives of this study were: a) to identify species of Cercospora spp. associated with PSS and CLB, verify the pathogenicity and quantify the concentration of cercosporin; b) to evaluate the effect of culture media on mycelial growth and sporulation of Cercospora cf. flagellaris; c) determine the effective concentration 50% (EC50) of triazole (DMI), morpholine (SBI), strobirulin (QoI), carboxamide (SDHI), benzimidazole (MBC) and multisite fungicides, and the sensitivity of C. cf. flagellaris isolates and d) determine the reaction of soybean cultivars to C. cf. flagellaris. In Chapter I, the isolates of Cercospora spp. were identified morphologically and molecularly, after which, the pathogenicity in soy plants and seeds was verified and the cercosporin concentration of these isolates was quantified. Thus, the 29 isolates identified were of the species C. cf. flagellaris (69%), C. canescens (14%), C. dichondrae (7%), C. helianthicola (4%), C. beticola (3%) and C. lagenariae (3%). The isolates were pathogenic to soybean, proving Koch's Postulates. The cercosporin concentration of the isolates ranged from 0.001 to 0.008 nmol/mL. In Chapter II, the effect of culture media on mycelial growth and sporulation of C. cf. flagellaris was evaluated. Seven culture media were used: BDA, PDA, AV8, ACZ, AEFS, ASS and AAV. As a result, the mycelial growth speed index and daily growth rate, were higher for the AAV culture medium for isolates UPF C01 and UPF C12. The culture media ACZ, AAV, AV8 and AEFS were better for the sporulation of the isolates. In Chapter III, the EC50 of fungicides and the sensitivity of isolates of the fungus were determined. As a result DMI fungicides showed EC50 from 0.014 to 63.09 mg.L-1, SBI fungicide showed EC50 from 0.07 to 0.81 mg.L-1, SDHI and multisite fungicides showed EC50 43.12 to >100 mg.L-1, QoI and MBC fungicides showed EC50 >100 mg.L-1. The isolates of C. cf. flagellaris were sensitive to the fungicides DMI and SBI, moderately sensitive to insensitive to the fungicides SDHI and multisite, and insensitive to the fungicides QoI and MBC. Chapter IV evaluated the reaction of 30 soybean cultivars to C. cf. flagellaris, inoculated by spraying the suspension of conidia and mycelium of the fungus. Thus, the highest severity of CLB was in the cultivars TMG7262 (2.67%), BRS6203 (2.63%) and BRS5601 (1.75%) for the isolate UPF C01, while for the isolate UPF C12, the cultivar with the highest severity was PIONEER 95R51 (1.83%).